CHARACTERIZATION OF THE OCCURRENCE OF FRACTURES IN THE ELDERLY: AN EPIDEMIOLOGICAL STUDY IN A PUBLIC HOSPITAL - Toneto, Michelle Aparecida dos Santos; Mendes, Paulo Cézar; Araújo, Suely Amorim de (Cogitare Enfermagem, 2024)
Objective: To find out about the main postoperative complications and the clinical outcome of elderly people after corrective fracture surgery. Method: a descriptive, cross-sectional study carried out in a public hospital in Minas Gerais, Brazil, between August and October 2021. Data was obtained through interviews and medical records and analyzed using the Chi-square and Fisher’s exact tests. Results: The main postoperative complications were pain, bleeding, and mental confusion. The variables correlated with the number of complications were outcome (p=0.016), ASA classification (p=0.047) and postoperative time (p=0.002). As for the type of fracture, it was the destination sector (p=0.002) and length of stay (p>0.0001). Conclusion: This study provides the team with greater knowledge about the profile of the elderly, to improve surgical planning and reduce the factors correlated with the presence of postoperative complications.